IMPORTANCE OF LEUCOCYTE ESTERASE TEST IN DIAGNOSIS OF URINARY TRACT INFECTION - PRIYANKA YADAV (MBBS); APARNA (MBBS, MD); MADHU SHARMA (MBBS, MD); UMA CHAUDHARY (MBBS, MD) (International Journal of Pharma and Bio Sciences, 2015)
Hospital diagnostic laboratories investigate many thousands of urine specimens each year, but only a small proportion(about 25-30%) of it are infected. Lot of staff time and culture material are spent on specimens that yield insignificant growth. Therefore, a simple inexpensive test is needed as a preliminary test in routine practice to select those urine samples only which require further examination in the laboratory. Leucocyte esterase test has the advantage of detecting esterases in both intact and lysed leucocytes. Therefore, even specimens that have not been preserved properly will yield a positive test result. The present study was designed to compare the reliability of wet mount examination and leucocyte esterase activity with that of a urine culture in diagnosing bacteriuria and pyuria in patients of UTIs. This study was conducted on a total of 600 urine samples received in the Microbiology department, Pt BDS PGIMS, Rohtak. The samples were processed as per standard procedures and subjected to microscopic examination, dipstick testing, TTC test and culture within 30 minutes of sample collection. Of 600 samples 144 were LET positive, of which 106 were positive by urine culture and 38 were urine culture negative. Similarly out of 600 samples 456 were LET negative, of which 417 were negative by urine culture while 39 were positive by urine culture. Out of the 145 culture positives, E. coli (44.1%) was most common pathogen. Conclusion: Rapid dipsticks tests for LET are reliable alternative to culture for screening of UTIs.